2021
DOI: 10.3390/rel12090766
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Religiosity during Suicide Bereavement: A Qualitative Systematic Review

Abstract: A loved one’s loss to suicide can be a traumatic experience and trigger a difficult grief process, identity changes, a loss of the sense of meaning and a spiritual crisis. Spirituality and/or religiosity (S/R) can be both an important resource and a source of stigmatisation during suicide bereavement. This study aims to synthesise the extant findings about S/R during suicide bereavement in qualitative studies. After an exhaustive selection of articles, the current review utilised a total of 484 citations and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
(195 reference statements)
1
13
0
Order By: Relevance
“…The stigma associated with suicide in the context of religions may be particularly strong, with some bereaved individuals choosing to hold private ceremonies following a suicide death [ 27 , 28 ]. This is supported by a qualitative systematic review that found that religious individuals often isolate themselves due to feelings of shame and suicide-related stigmatisation emanating from religious doctrines [ 29 ]. Interestingly, taking part in religious ceremonies was common practice even in those participants who identified as agnostic [ 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…The stigma associated with suicide in the context of religions may be particularly strong, with some bereaved individuals choosing to hold private ceremonies following a suicide death [ 27 , 28 ]. This is supported by a qualitative systematic review that found that religious individuals often isolate themselves due to feelings of shame and suicide-related stigmatisation emanating from religious doctrines [ 29 ]. Interestingly, taking part in religious ceremonies was common practice even in those participants who identified as agnostic [ 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…Studies reveal that higher religiosity and positive spiritual/religious coping are related to better bereavement outcomes [ 28 , 29 , 56 , 57 ]. The sense of presence and continuing the bond with the deceased as an outer figure can be helpful during bereavement to assure the existence of the afterlife with a hope to meet again and not lose the connection to the loved one [ 6 , 8 , 23 ]. Our study revealed an additional aspect of spiritual resources during bereavement being perceived as activated without one’s wish.…”
Section: Discussionmentioning
confidence: 99%
“…If a person is highly religious, the answers might be easier to find [ 24 ]. However, the questions and experiences also visit non-religious people [ 8 ], which adds the interdisciplinary phenomenon of spirituality to the psychological issues of suicide bereavement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations